Rubem Fonseca: Violência E Dualidade Nas Vozes Narrativas - Fernandes, Juliana Pires [UNIFESP] (2018)
This M.A. Thesis Proposes An Investigation Of The Manifestations Of Violence And Marginality In Rubem Fonseca"S Books Of Short Stories Feliz Ano Novo (1975) And O Cobrador (1979). It Analyses, Regarding The Point Of View, How Far The Linguistic Choices Are Close To Or Distant From The Constructions Of The Narrators Of The Tales. If The Brutal Language, Present In Both Collections, Seems To Emerge Under The Premise Of Being Fundamental To The Coherent Construction Of The First-Person Narrators, Marked In Their Vast Majority By Some Or Several Traces Of Marginality, It Is Also Opposed To Another Language, With Introspective, Literary And Reflexive Characteristics. The Juxtaposition Of These Dissonant Voices In The Literary Works " Voices Of Culture And Of Barbarity " Gives The Opportunity To Hypothesize About The Meanings That Originate From The Duality. In View Of The Fact That Violence Belongs To Very Different Discourses And Speakers, With Complex And Heterogeneous Bonds To Culture And Barbarity, It Seems Pl